Renal Clear Cell Carcinoma and Tonsil Metastasis - Dario Marcotullio; Giannicola Iannella; Gian Franco Macri; Caterina Marinelli; Melissa Zelli; Giuseppe Magliulo (Case Reports in Otolaryngology)
Renal cell carcinoma is the most common renal tumor in adults. Clear cell carcinoma represents 85% of all histological subtypes. In February 2012 a 72-year-old woman came to our department due to the appearance of massive hemoptysis and pharyngodinia. Previously, this patient was diagnosed with a renal cell carcinoma treated with left nephrectomy. We observed an exophytic, grayish, and ulcerated mass in the left tonsillar lodge and decided to subject the patient to an immediate tonsillectomy. Postoperative histology showed nests of cells with highly hyperchromatic nuclei and clear cytoplasm. These features enabled us to make the diagnosis of renal clear cell carcinoma metastasis. Only few authors described metastasis of renal cell carcinoma in this specific site.